The influence of sitting posture on mechanics and metabolic energy requirements during sit-skiing: a case report - Hofmann, K. B.; Ohlsson, M. L.; Höök, M.; Danvind, J.; Kersting, U. G. (Sports Engineering, 2016)
Several different sitting postures are used in Paralympic cross-country sit-skiing. The aim of this study was to evaluate the impact of sitting posture on physiological and mechanical variables during steady-state double-poling sit-skiing, as well as to determine how seat design can be improved for athletes without sufficient trunk control. Employing a novel, custom-designed seat, three trunk positions were tested while performing double-poling with submaximal oxygen consumption on an ergometer. Cycle kinematics, pole forces, and oxygen consumption were monitored. The athlete performed best, with longer cycle length and less pronounced metabolic responses, when kneeling with the trunk resting on a frontal support. For this case, a forward leaning trunk with knees below the hip joint was interpreted as most optimal, as it showed lower oxygen consumption and related parameters of performance during cross-country sit-skiing. Further investigations should examine whether such improvement is dependent on the level of the athlete`s handicap, as well as whether it is also seen on snow.